Memutar Sejarah â€œGambar Idoepâ€ Masa Silam: Industri Perfilman dan Dampaknya di Medan pada Era Kolonial Belanda sampai Orde Baru - Batubara, Taslim (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
This article discusses the history of the film and cinema industry in Medan in the Dutch Colonial era until the New Order. Initially, the term film was more familiar with the name â€œGambar Idoepâ€ or â€œLayar Tancapâ€. Films entered in Indonesia were brought by the Dutch people. This research uses the historical method by conducting a study of a number of libraries, especially the De Sumatra Post newspaper and is supported by other references from books, magazines, journals which the author considers appropriate and credible. The findings of this study were that in the beginning, cinema was only intended by the elite and Europeans. However, after the Ethical Politics the film can be enjoyed by everyone. Films reached Medan in the late 19th century. The first cinema that was built in Medan was De Oranje Bioscoop in 1889. Then it was followed by other theaters that enlivened the entertainment business in Medan. In its journey, this industry has gone through many challenges of the times. The cinema comes as a cheap and quality new entertainment facility. In addition, the cinema is also a meeting place of various cultures and social status.Keywords: Film history, cinema, entertainment business.